Knowledge and awareness of the Klinefelter Syndrome among the dental students - Ashwin Jaikumar Ram; Vishnupriya Veeraraghavan; J Selvaraj; R Gayathri; S Kavitha (Wolters Kluwer Medknow Publications, 2022)
The presence of one or more extra X chromosomes in a male causes Klinefelter Syndrome (KS). KS affects 1 in 500-1 in 1000 men, while about half remain undiagnosed. KS is characterized by huge stature, increase in arm length, the feminine distribution of adipose tissues (including gynecomastia), less or pubic hair, infertility, hypotonia, reduced size of penis and less than average verbal IQ, struggle in learning and requirements for less specified speech therapy. KS is a primary testicular insufficiency with high levels of gonadotropin caused by a lack of pituitary gland feedback. The aim of the study is to assess the knowledge and awareness of the KS among the dental students. This cross-sectional survey was conducted among dental students of a private dental hospital. To evaluate the knowledge and awareness of the participants about KS, a self-administered questionnaire consisting of 10 questions was prepared. Percentage analysis and frequency analysis and percentage analysis were performed. A Chi-square test was done to assess the correlation using the SPSS software. In our study, most of the participants were aware of the KS. They also knew that the KS is caused due to the additional X chromosome. We would like to conclude that the dental students were much aware about the Klinefelter and they also had a thorough knowledge about it.